ATTITUDE TO HEALTH AND MOTIVATION TO QUIT SMOKING IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - E. D. Chetverkina; A. G. Kozyrev; G. A. Ivanova; E. R. Isaeva; A. I. Kirillova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
The work is devoted to study of features of the status of smoking in patients with the chronic obstructive pulmonary disease (COPD). Degree of nicotine addiction, types of smoking behavior in various age groups of patients are determined. The interrelation at sick HOBL between motivation to refusal of smoking and the attitude towards health is analyzed. The directions of psychotherapeutic impacts for increase in efficiency of the techniques directed to refusal of smoking are offered.Objective  – to study the motivation to quit smoking and attitudes towards health in patients with COPD. Materials  and  methods. A questionnaire by D. Horney for determining the type of smoking behavior; Fagerstrem test for the determination of nicotine dependence; the questionnaire for determining the motivation to refuse to smoke; the questionnaire of N.E. Vodopyanova «Assessment of the level of satisfaction with the quality of life» (2005) and the methodology «Attitude to health» by R. A. Berezovsky.Results.  The average age for the entire sample of respondents was 65.3±7.6 years, the length of smoking in smokers was 33.5±14.3 years. The predominant type of smoking behavior in the survey sample was «Support». In patients with high motivation, the assessment of the level of satisfaction with the overall «quality of life index» (ICI) was 26 points. In patients with low motivation to quit smoking, the mean value (ICR) was 21.Conclusion. Patients with high motivation to quit smoking were older than patients with low motivation. A group of patients with COPD with high motivation to quit smoking was characterized mainly by low or medium degree of nicotine dependence; the dominant type of smoking behavior of them was «Support.» On the contrary, in the group of patients with low motivation, physical dependence on nicotine prevailed; the «thirst» was the dominant type of smoking behavior.